PENGARUH PERCEIVED RISK, COST SAVING, DAN TIME SAVING TERHADAP KEPUASAN PELANGGAN PADA PEMBELIAN TIKET PESAWAT ONLINE DI SITUS TIKET2 - Septi Ambarwati; Endro Isnugroho (STIE Pariwisata API Yogyakarta, 2018)
This research explains the effect of perceived risk, cost saving, and time saving on customer satisfaction on the purchase of airline tickets online through website tiket2. It is based on information technology quality in selling tickets online by providing features that are very easy to use, and give serious attention to the security of customer data and ease in transacting. This research uses non probability sampling method with the criteria used in sample selection is customer who make ticket purchase through website tiket2. The data used in this study is primary data obtained directly from respondents through interviews and filling questionnaires. From the results of research proved perceived risk, cost saving, and time saving have a positive and significant impact on customer satisfaction. The contribution of this research is expected to be as an input and guide for management practitioners in carrying out business activities, especially those related to factors that influence customer satisfaction, that is, to provide input in decision making at giving satisfaction to the customer.Keywords: perceived risk, cost saving, time saving, customer satisfaction, non probability sampling